Effect of fertilization on the accumulation and health risk for heavy metals in native Andean potatoes in the highlands of Perú - Orellana Mendoza, Edith; Camel Paucar, Vladimir Fernando; Yallico Madge, Luz Consuelo; Quispe Coquil, Violeta; Cosme De la Cruz, Roberto Carlos (Elsevier, 2024)
Soil infertility is a global problem, amendments such as organic fertilizers and mineral fertilizers are used to improve crop yields. However, these fertilizers contain heavy metals as well as essential mineral elements. The objective of the study was to determine the effect of organic and inorganic fertilizer on the accumulation and health risk of heavy metals in tubers. The plants were cultivated at an altitude of 3970 m using four treatments (poultry manure, alpaca manure, island guano and inorganic fertilizer) and a control group. Soil contamination levels and the degree of metal accumulation in the tubers were also determined. As a result, it was found that the use of inorganic fertilizer and poultry manure increased the values of Cu and Zn in soils, exceeding the recommended standards. The accumulation of heavy metals in potato tubers did not exceed the maximum recommended limits with the exception of Pb, which exceeded the limit allowed by the FAO/WHO (0.1 mg kg−1). Poultry manure contributed to the highest accumulation of Zn, Cu and Pb in tubers with 11.62±1.30, 3.48±0.20 and 0.12 ±0.02 mg kg-1 respectively. The transfer of metals from the soil to the tubers was less than 1. Individual and total non-carcinogenic risk values were less than 1, indicating a safe level of consumption for children and adults. The cancer risk was found to be within an acceptable range. However, poultry manure and inorganic fertilizer treatments had the highest total cancer risk values in both age groups, suggesting a long-term carcinogenic risk.